Oxidized alginate hydrogels for BMP-2 delivery in long bone defects - Priddy, Lauren B (2014)
Autograft treatment of large bone defects and fracture non-unions is complicated by limited tissue availability and donor site morbidity. Polymeric biomaterials such as alginate hydrogels provide an attractive tissue engineering alternative due to their biocompatibility, injectability, and tunable degradation rates. Irradiated RGD-alginate hydrogels have been used to deliver proteins such as bone morphogenetic protein-2 (BMP-2), to promote bone regeneration and restoration of function in a critically sized rat femoral defect model. However, slow degradation of irradiated alginate hydrogels may impede integration and remodeling of the regenerated bone to its native architecture. Oxidation of alginate has been used to promote degradation of alginate matrices. The objective of this study was to evaluate the effects of alginate oxidation on BMP-2 release and bone regeneration. We hypothesized that oxidized-irradiated alginate hydrogels would elicit an accelerated release of BMP-2, but degrade faster in vivo, facilitating the formation of higher quality, more mature bone compared to irradiated alginate. Indeed, oxidation of irradiated alginate did accelerate in vitro BMP-2 release. Notably, the BMP-2 retained within both constructs was bioactive at 26 days, as observed by induction of alkaline phosphatase activity and positive Alizarin Red S staining of MC3T3-E1 cells. From the in vivo study, robust bone regeneration was observed in both groups through 12 weeks by radiography, micro-CT analyses, and biomechanical testing. Bone mineral density (BMD) was significantly greater for the oxidized-irradiated alginate group at 8 weeks. Histological analyses of bone defects revealed enhanced degradation of oxidized-irradiated alginate and suggested the presence of more mature bone after 12 weeks of healing.